PARENTAL INFLUENCE ON CHILDREN'S READING HABITS - Wahyuningsih, Nandini Eka; Maghfiroh, Ana; Sugianto, Alip; Laksana, Sigit Dwi (TARBAWI:Journal on Islamic Education, 2025)
This study aims to explore the role of parents in developing children's reading habits to improve their academic performance. This study aims to determine the role, influence and strategies of parents on children's learning development and forming reading habits. This study uses a qualitative method with an interpretive paradigm in learning and readingData were collected through semi-structured interviews with parents and documentation. Then the data were analyzed and transcribed thematically. The results showed that parental involvement in reading activities was positively related to children's academic success. This study also highlighted the influence of parenting styles on children's learning motivation. The results of this study emphasize the importance of comprehensive interventions that target parenting practices and children's learning environments to optimize educational outcomes.